원격측정 실시간 자료처리 프로그램의 실시간 그래프 최적화 - 김동영; Dong-young Kim; 노윤희; Yun-hee Ro; 황치호; Chi-ho Hwang; 임수열; Soo-yeol Im (한국항행학회논문지, 2025)
원격측정 시스템은 비행체로부터 데이터를 획득하여 지상으로 송신하는 시스템이다. 원격측정 시스템을 통해 수신한 데이터로 비행체의 현재 상태를 실시간으로 모니터링하기 위한 원격측정 실시간 자료처리 프로그램이 개발되었다. 지속적인 비행체의 개발로 계측 데이터가 증가하고 있으며, 이에 따라 프로그램 사용자의 요구가 다양해지고 있다. 고용량 데이터 분석, 여러 개의 분석 도구 배치, 다중 모니터 사용, 그리고 긴 시간 동안의 데이터를 효과적으로 분석하고자 한다. 그러나 과도한 전시 환경을 구성한 경우 시스템 성능 저하가 발생하였고, 이는 실시간 그래프에 대용량 포인트를 렌더링할 때 메모리 사용량 증가로 인한 가비지 컬렉터의 수행 빈도 증가가 원인이었다. 본 논문에서는 이를 해결하기 위해 실시간 그래프 최적화 알고리즘을 제안하고 구현하였으며, 다양한 환경에서의 테스트를 통해 제안한 알고리즘의 성능을 검증하였다. A telemetry system is a system that acquires data from an aircraft and transmits it to the ground. Real-time data processing program for Telemetry was developed to monitor the current state of the aircraft in real time using data received through a telemetry system. Measurement data is increasing due to the continuous development of aircraft, and accordingly, the needs of program users are diversifying. There is a need for high-capacity data analysis, multiple analysis tools deployment, using multiple monitors, and effective analysis of long-duration data. However, when an excessive display environment was configured, system performance degradation, and the cause was an increase in the frequency of garbage collector execution due to increased memory usage when rendering a large number of points on a real-time graph. In this paper, a real-time graph optimization algorithm was proposed and implemented to solve this problem, and the performance of the proposed algorithm was verified through tests in various environments.